2021
DOI: 10.1101/cshperspect.a041268
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Compartments: An Incomplete Primer to Nuclear Compartments, Bodies, and Genome Organization Relative to Nuclear Architecture

Abstract: This work reviews nuclear compartments, defined broadly to include distinct nuclear structures, bodies, and chromosome domains. It first summarizes original cytological observations before comparing concepts of nuclear compartments emerging from microscopy versus genomic approaches and then introducing new multiplexed imaging approaches that promise in the future to meld both approaches. I discuss how previous models of radial distribution of chromosomes or the binary division of the genome into A and B compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(49 citation statements)
references
References 241 publications
0
48
0
1
Order By: Relevance
“…SRRM2 is a nuclear speckle protein and spliceosome component, and RNA transcription splicing have been reported to take place at or in close proximity to nuclear speckles (Belmont, 2021; Chen and Belmont, 2019). A recent model suggested that splice-site selection is regulated by partial immersion of unspliced pre-mRNA at the interface between nuclear speckles and nucleoplasm (Liao and Regev, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…SRRM2 is a nuclear speckle protein and spliceosome component, and RNA transcription splicing have been reported to take place at or in close proximity to nuclear speckles (Belmont, 2021; Chen and Belmont, 2019). A recent model suggested that splice-site selection is regulated by partial immersion of unspliced pre-mRNA at the interface between nuclear speckles and nucleoplasm (Liao and Regev, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Physical maps of nuclear landscapes, supplemented with biochemical information about epigenetic markers and attachment sites of specific macromolecules and functional complexes, have revolutionized our views on nuclear organization. How nuclear compartments are established and maintained, and how they interact functionally, has remained a largely unsolved problem (Belmont, 2021;Misteli, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Euchromatin and heterochromatin are known to exhibit distinct chemical modifications [27][28][29][30] and interact with different regulatory proteins 28,29 and nuclear bodies. 9,[31][32][33] The chemical modifications themselves could drive chromatin demixing by altering nucleosome interactions. For example, acetylation could neutralize the positive charges on histone tails to weaken their binding with DNA, [34][35][36][37] while methylation may lead to under-twisted DNA that strengthens its interactions with histones.…”
Section: Introductionmentioning
confidence: 99%